2015
DOI: 10.1371/journal.pone.0131027
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Eating Disorders and Depression in Emerging Adults with Early-Onset, Long-Duration Type 1 Diabetes and Their Association with Metabolic Control

Abstract: BackgroundThis study analyzed the prevalence of and association between symptoms of eating disorders and depression in female and male emerging adults with early-onset, long-duration type 1 diabetes and investigated how these symptoms are associated with metabolic control.MethodsIn a nationwide population-based survey, 211 type 1 diabetes patients aged 18-21 years completed standardized questionnaires, including the SCOFF questionnaire for eating disorder symptoms and the Patient Health Questionnaire (PHQ-9) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 50 publications
(64 reference statements)
3
27
1
4
Order By: Relevance
“…21 Furthermore, concurrent mental health problems (e.g., depressive symptoms) may be associated with the prevalence of disordered eating and metabolic outcomes, as previously shown for young adults with early-onset T1D. 22,23 In conclusion, disordered eating and IR are common among youths with early-onset and longduration T1D and are associated with poor metabolic outcomes. Future studies should analyze reasons for and predictors of disordered eating and IR, examine the potential benefits of short screening instruments such as the SCOFF in patient groups, and develop and evaluate strategies for early…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…21 Furthermore, concurrent mental health problems (e.g., depressive symptoms) may be associated with the prevalence of disordered eating and metabolic outcomes, as previously shown for young adults with early-onset T1D. 22,23 In conclusion, disordered eating and IR are common among youths with early-onset and longduration T1D and are associated with poor metabolic outcomes. Future studies should analyze reasons for and predictors of disordered eating and IR, examine the potential benefits of short screening instruments such as the SCOFF in patient groups, and develop and evaluate strategies for early…”
Section: Discussionmentioning
confidence: 78%
“…Once established, disordered eating is highly persistent, with the potential to progress to full‐blown EDs . Furthermore, concurrent mental health problems (e.g., depressive symptoms) may be associated with the prevalence of disordered eating and metabolic outcomes, as previously shown for young adults with early‐onset T1D …”
Section: Discussionmentioning
confidence: 89%
“…In our study, a prior diagnosis of depression or anxiety was not associated with DE behaviours. Other studies have shown that young adults with T1D who screened positive for DE have more severe depressive symptoms . Neither of these studies used screening tools that were specific to the T1D population when looking at the prevalence of DE.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that young adults with T1D who screened positive for DE have more severe depressive symptoms. 25,26 Neither of these studies used screening tools that were specific to the T1D population when looking at the prevalence of DE. Bachle et al, found that a minority of young adults with depressive symptoms met DSM-V criteria for depression, which may account for why no association was seen in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation